2002
DOI: 10.1038/sj.gene.6363868
|View full text |Cite
|
Sign up to set email alerts
|

Tunisian endemic pemphigus foliaceus is associated with desmoglein 1 gene polymorphism

Abstract: Desmoglein 1 is the target antigen and probably the initiating immunogen of the autoantibody response in pemphigus foliaceus (PF),Pemphigus foliaceus (PF) is an autoimmune blistering skin disease characterized by superficial epidermal blisters and the production of pathogenic autoantibodies directed against desmoglein 1, a 160-kDa transmembrane desmosomal glycoprotein belonging to the cadherin superfamily. 1 Two different varieties of PF have been identified. The sporadic form occurs in western Europe and Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
(11 reference statements)
0
12
0
1
Order By: Relevance
“…Autoimmune bullous skin diseases were unexpectedly relatively frequent representing up to 5% of all histological diagnoses every year. Since most of the affected patients live in the area of the Mount Kilimanjaro and because of clinical and epidemiological peculiarities we have a suspect that they may have an endemic type of pemphigus foliaceus, as found in North Africa …”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune bullous skin diseases were unexpectedly relatively frequent representing up to 5% of all histological diagnoses every year. Since most of the affected patients live in the area of the Mount Kilimanjaro and because of clinical and epidemiological peculiarities we have a suspect that they may have an endemic type of pemphigus foliaceus, as found in North Africa …”
Section: Discussionmentioning
confidence: 99%
“…In spite of the structural variation of the protein, resulting from the exon 11 polymorphism, the lack of association in all three populations thus far analyzed (French, Tunisian and Brazilian; Martel et al [6], Ayed et al [7] and this study, respectively) allows to conclude that the structural variation in the EA domain plays no role in differential susceptibility to pemphigus foliaceus. Interestingly, anti-EA antibodies are common in individuals without skin disease living in endemic areas [17].…”
Section: Discussionmentioning
confidence: 51%
“…We conclude that the analyzed genetic variability of the autoantigen dsg1 is not a critical factor modulating susceptibility to this disease. Nevertheless, it should be noticed that there is a consistent tendency towards a higher frequency of variant 809 C and of C/C homozygotes in pemphigus patients, in all three populations analyzed [for genotype C/C, French: OR Z 2.9, P Z 0.03 [8]; Tunisian: OR Z 1.7, P Z 0.046 [7]; Brazilian, this study: OR Z 1.5, P Z 0.078]. Whether this reflects a real slight influence of desmoglein 1 genetic variability on disease susceptibility remains to be proven.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Genetic studies to date have identified associations between PF and the class II major histocompatibility class (MHC) genes encoding for human leucocyte antigen (HLA)‐DR and HLA‐DQ, as well as Dsg1 and some cytokines, notably interleukins (IL)‐4 and IL‐6 . Population association studies with HLA‐DR and HLA‐DQ antigens have been conducted in both endemic and sporadic PF .…”
Section: Introductionmentioning
confidence: 99%